Accelerated Development of the Tourism Industry in the Republic of Uzbekistan - Kakhkharov, Jakhongir; Makushina, Alla; Umarov, Abduvahob; Ambartsumyan , Anastas (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the theoretical and practical aspects of the development of the tourism industry in the world and the Republic of Uzbekistan. The statistics on the development of this industry on a global scale, as well as in the Republic of Uzbekistan, is given. The features of the development of this sphere in Uzbekistan, significant potential for the development of international tourism in Uzbekistan are considered in this article. The article also considers the legal base that contributes to the development of tourism in the Republic of Uzbekistan and describes cooperation with international organizations. The article also identified problems in the development of the tourism industry in the Republic of Uzbekistan. The recommendations for further development of tourism in Uzbekistan are given.